Inflammatory reaction and tensile strength of the abdominal wall after an implant of polypropylene mesh and polypropylene/poliglecaprone mesh for abdominal wall defect treatment in rats - Biondo-Simões,Maria de Lourdes Pessole (2014)
PURPOSE: To compare the inflammatory reaction and the growing resistance of the abdominal wall with the use of poliglecaprone meshes and polypropylene meshes associated with poliglecaprone in the correction of abdominal defects. METHODS: Seventy-seven Wistar rats were divided into three groups: CG (non-operated animals: EG (polypropylene mesh) and UG (polypropylene and poliglecaprone mesh). A muscular and aponeurotic defect was formed and treated according to the group. Evaluations were made after 4, 7, 14, 28 and 56 days. The resistance and inflammatory pattern were studied. RESULTS: There was a gradual and significant gain in resistance, regularly in the EG and irregularly in the UG, which was lower on the 14th day (p=0.008). The inflammatory reaction was acute and more intense in the UG on the fourth day. At all other times, the inflammatory pattern was acute to chronic, similar in both groups, with minimum intensity on the 56th day. CONCLUSION: The greater resistance offered by the polypropylene mesh was regular and ascending, stabilizing on the 28th day, while that of the polypropylene/poliglecaprone was not even. In the end, the resistances were similar. The inflammatory response was greater in the UG on the fourth day and similar at all other times.